THEORETICALLY - THE LEGAL IDEA OF THE EUROPEAN UNION - Бородін, Іван Лук`янович; Варава, Ірина Павлівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose the article consists in an analysis of the formation and modern state of development of the European Union, and there is also an attempt to indicate certain historical prerequisites for the emergence of the idea of this Union and its right regulation. Methods: comparison, analysis, analogy, historicism, and others, which made it possible to achieve the goal in a logical sequence - to show the characteristic features of European integration processes in connection with the pace of globalization on the European continent, to analyze the legal content of certain components of legal acts that form the basis of the idea of the European Union. Results: the problems of the theory and practice of European integration are considered from the point of view of scientific traditions that have developed as a result of research in this direction, as a result of which it is explained that the idea of the European Union on the European continent is historically conditioned. The need to unite the countries of Europe is aimed at jointly solving geopolitical and economic problems. Discussion: the unification of Western Europe into the European Union was carried out on the basis of such principles, which made it possible to solve a number of economic and political problems that are important for EU member states. Now, with the strengthening of the European Union, the problem arises of ensuring the mechanism of interaction between the Union authorities and the governing bodies of the Union states. There is a need to improve the structure of the European Union, to develop the process of its unification. On the basis of history, the modern state of European integration processes, the task is set to assess the political and legal legitimacy of the European Union. The theoretical - legal problems of the idea of the European Union have not yet been fully investigated. This topic is relevant in the legal, political and sociological sciences of the States members of the European Union and other States of the European continent. The need to continue the study of modern theoretical and legal problems of European integration remains.